Proactive career behaviors and subjective career success: The moderating role of national culture. (20th August 2018) - Smale, Adam; Bagdadli, Silvia; Cotton, Rick; Dello Russo, Silvia; Dickmann, Michael; Dysvik, Anders; Gianecchini, Martina; Kaše, Robert; Lazarova, Mila; Reichel, Astrid; Rozo, Paula; Verbruggen, Marijke; et al.
Summary: Although career proactivity has positive consequences for an individual's career success, studies mostly examine objective measures of success within single countries. This raises important questions about whether proactivity is equally beneficial for different aspects of subjective career success, and the extent to which these benefits extend across cultures. Drawing on Social Information Processing theory, we examined the relationship between proactive career behaviors and two aspects of subjective career success—financial success and work‐life balance—and the moderating role of national culture. We tested our hypotheses using multilevel analyses on a large‐scale sample of 11, 892 employees from 22 countries covering nine of GLOBE's 10 cultural clusters. Although we found that proactive career behaviors were positively related to subjective financial success, this relationship was not significant for work‐life balance. Furthermore, career proactivity was relatively more important for subjective financial success in cultures with high in‐group collectivism, high power distance, and low uncertainty avoidance. For work‐life balance, career proactivity was relatively more important in cultures characterized by high in‐group collectivism and humane orientation. Our findings underline the need to treat subjective career success as a multidimensional construct and highlight the complex role of national culture in shaping the outcomes of career proactivity.